Impact of perceived website cues on purchase experience and e-purchase intention of online apparel buyers. (8th February 2022) - Dua, Pallavi; Uddin, S.M. Fatah
The purpose of this research is to evaluate the impact of perceived website cues of apparel retailers' websites on customers' purchase experience and online buying intention of apparel consumers. For this, survey data was collected with the help of a structured questionnaire using five-point Likert scale from 160 working professionals within the age group of 25-60 years from Delhi/NCR region employing purposive and quota sampling. Exploratory factor analysis revealed existence of four apparel website attributes namely product information, privacy and security, customer service and navigation. Regression analysis results showed that there is a significant influence of privacy and security, customer service and navigation attributes of apparel websites on buyers purchase experience and e-purchase intention. The paper attempts to fill the void in the literature by shedding light on the influence of apparel website cues on purchase experience and e-purchase intention of Generation X and Generation Y apparel buyers.